Translational Studies on Inflammation - Nunes, Ane C.F (IntechOpen, 2020)
Inflammation is known worldwide, from the bench to the bedside, but it is a hard theme to approach with one single point of view.In this sense, a selection of translational studies would support the medical-scientific community to better understand the complex network of the inflammatory process, its maintenance, and potential treatment targets. The eleven chapters that compose this book present interesting insights into inflammation and its mechanisms, merging classic background with innovative approaches. From the molecular basis to experimental models, the chapters selected for this book bring to readers at different academic levels updated and practical data on inflammation. Find out what drives interdisciplinary medical research on inflammation and enjoy this informative collection.